2008
DOI: 10.1080/00914030701476915
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Agro-Wastes and Crustacean Fillers on Poly (Vinyl-Acetate) Emulsion Wood Adhesives

Abstract: Cellulosic and crustacean filler materials were used to study their effects on poly(vinyl-acetate) (PVAC) emulsion wood adhesives. The elastoplastic behavior of the filler-treated PVAC emulsion was studied using differential scanning calorimetry and dynamic mechanical thermal analysis. The result revealed that the glass transition temperature (Tg) of the filler-treated polymer is not significantly changed by the addition of the filler materials, whereas the tensile modulus, adhesive hardness, and the stiffness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Clearly seen, viscosity increased with increasing bark filler ratio. Ogban and Ogbobe [14] stated that the increased viscosity of glue mixtures is due to the high oil absorption ability of cellulosic filler. Figure 1 showed that initial viscosity of glue mixtures with BN bark filler was higher than glue mixtures with DB bark filler.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly seen, viscosity increased with increasing bark filler ratio. Ogban and Ogbobe [14] stated that the increased viscosity of glue mixtures is due to the high oil absorption ability of cellulosic filler. Figure 1 showed that initial viscosity of glue mixtures with BN bark filler was higher than glue mixtures with DB bark filler.…”
Section: Resultsmentioning
confidence: 99%
“…Viscosity's adhesive plays an important role in gluing process, since too high or too low viscosity gives a low bonding strength [8]. Too viscous adhesives are difficult to spread out and much of adhesives are remain on wood surface, hence decrease the efficiency contact area between wood and adhesives [14,15]. It leads to weak the bonding strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation